Regenerative therapies for myocardial infarction: exploring the critical role of energy metabolism in achieving cardiac repair - Jiahao Ren; Xinzhe Chen; Tao Wang; Cuiyun Liu; Kun Wang (Frontiers in Cardiovascular Medicine)
Cardiovascular diseases are the most lethal diseases worldwide, of which myocardial infarction is the leading cause of death. After myocardial infarction, in order to ensure normal blood supply to the heart, the remaining cardiomyocytes compensate for the loss of cardiomyocytes mainly by working at high capacity rather than by proliferating to produce new cardiomyocytes. This is partly due to the extremely limited ability of the adult heart to repair itself. A growing body of research suggests that the loss of cardiac regenerative capacity is closely related to metabolic shifts in energy sources. Currently, a large number of studies have focused on changes in metabolic levels before and after the proliferation window of cardiomyocytes, so it is crucial to search for relevant factors in metabolic pathways to regulate the cell cycle in cardiomyocyte progression. This paper presents a review of the role of myocardial energy metabolism in regenerative repair after cardiac injury. It aims to elucidate the effects of myocardial metabolic shifts on cardiomyocyte proliferation in adult mammals and to point out directions for cardiac regeneration research and clinical treatment of myocardial infarction.